2015
DOI: 10.1186/s12929-015-0172-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the potential of Shikonin as a novel hypertrophic scar treatment

Abstract: BackgroundHypertrophic scarring is a highly prevalent condition clinically and results from a decreased number of apoptotic fibroblasts and over-abundant production of collagen during scar formation following wound healing. Our previous studies indicated that Shikonin, an active component extracted from Radix Arnebiae, induces apoptosis and reduces collagen production in hypertrophic scar-derived fibroblasts. In the study reported here, we further evaluate the potential use of Shikonin as a novel scar remediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
1
17
1
Order By: Relevance
“…Thus, it is plausible that the down-regulation of inflammatory cytokines and MMPs that we observed in hPDLCs following treatment with SHI may be mediated by the inhibitory effect of SHI on NF-jB activation. In our previous publication, SHI was found to increase the phosphorylation of NF-jB and reduce the phosphorylation of I-jB in human dermal fibroblasts (Fan et al 2015). Interestingly, we did not observe the equivalent response to SHI on the phosphorylation of I-jB in hPDLCs in this study.…”
Section: Discussioncontrasting
confidence: 83%
“…Thus, it is plausible that the down-regulation of inflammatory cytokines and MMPs that we observed in hPDLCs following treatment with SHI may be mediated by the inhibitory effect of SHI on NF-jB activation. In our previous publication, SHI was found to increase the phosphorylation of NF-jB and reduce the phosphorylation of I-jB in human dermal fibroblasts (Fan et al 2015). Interestingly, we did not observe the equivalent response to SHI on the phosphorylation of I-jB in hPDLCs in this study.…”
Section: Discussioncontrasting
confidence: 83%
“…Shikonin in cancer lines has been shown to alter a number of intracellular signalling pathways particularly those associated with apoptosis [ 103 105 ]. Fan and colleagues demonstrated that Shikonin keratinocytes did not respond to Shikonin unlike human scar-derived fibroblasts which where stimulated to undergo apoptosis [ 106 ]. Shikonin induced apoptosis by altering the expression of capsase-3, B-cell lymphoma (BCL)-2, phosphorylation of ERK1/2 and p38 [ 107 ].…”
Section: Reviewmentioning
confidence: 99%
“…Liver injury observed at doses of 90 mg/kg and above [ 138 ] • Bardoxolone methyl—semi-synthetic triterpenoid based on the scaffold of oleanolic acid—caused heart failure in patients with stage 4 chronic kidney disease [ 139 ] Curcumin Rhizome of Curcuma longa and related species. • Induced fibroblast apoptosis and reduced collagen gel contraction [ 99 ] via ROS mechanism • In vitro (human fibroblasts) [ 99 ] • Poor bioavailability especially after oral administration [ 164 ] • Appears well tolerated up to 8 g/day up to 3 months [ 164 , 165 ] • Adverse effects may change with adaptations that are used to improve bioavailability • Chelate iron suppresses hepcidin therefore potentially causing iron deficiency [ 166 ] • Interacts with 5-fluorouracil and vinorelbine [ 140 , 147 , 148 , 156 ] Shikonin Chinese herb Radix Arnebiae • Induces apoptosis in fibroblasts [ 106 ] • Down-regulates collagen types I and III and α smooth muscle actin [ 107 ] • Appears to induce apoptosis by altering p-ERK 1/2, p-p38 and caspase-3 [ 107 ] • In vitro (human keratinocytes, skin fibroblasts) [ 106 ] • In vitro (human keratinocytes, human skin fibroblasts, hypertrophic scar-derived fibroblasts) [ 107 ] • Low bioavailability due to high lipophilicity [ 167 ] altered through the formation of a complex with other proteins [ 150 ] • Limited toxicity studies—one animal study demonstrated that it appeared safe up to concentrations of 800 mg/kg for 180 days [ 168 ] Emodin Derived from the Himalayan rhubarb, buckthorn and Japanese knotweed • Alters the intracellular pathway of Pi3K and Akt but only in hypertrophic scar-derived fibroblasts [ 113 ] and this in turn inhibited the inflammatory response and improved the histopathology appearance of the scar [ 113 ] • In vivo and in vitro (mice model for hypertrophic scars, emodin was administered intra-peritoneally; mice derived hypertrophic scarring fibroblasts and normal fibroblasts) [ 113 ] …”
Section: Reviewmentioning
confidence: 99%
“…Shikonin (C16H16O5), a natural naphthoquinone extracted from Radix Arnebiae, has been widely demonstrated to possess various biological activities, such as anti-inflammatory, anti-bacterial, anti-angiogenic, and anti-tumorigenic properties ( Hashimoto et al, 1999 ; Chen et al, 2002 ; Gao et al, 2002 ; Hsu et al, 2004 ; Chang et al, 2010 ). We have previously reported that Shikonin inhibits cell proliferation, induces apoptosis and reduces collagen production in vitro ; and may therefore hold potential as a novel scar remediation therapy ( Fan et al, 2015a , b ; Xie et al, 2015 ). In the current study, we aimed to validate the potential of Shikonin for scar remediation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin, a key ingredient of the herb Radix arnebiae, possesses various biological activities, such as anti-tumourigenic, anti-oxidant, anti-bacterial, and anti-inflammatory properties ( Hsu et al, 2004 ). We have previously reported that Shikonin induces apoptosis and reduces collagen production in hypertrophic scar fibroblasts in vitro ( Fan et al, 2015a , b ; Xie et al, 2015 ). and may therefore hold potential as a novel scar remediation therapy.…”
Section: Introductionmentioning
confidence: 99%